Type I disc herniation in Dachshound (Veterinary Science, 2020)
Disc Hernia type I is a condroid degeneration that leads to calcification of the pulpy nucleus and the consequent loss of the hydroelastic properties of intervertebral disc. Its presentation is most common in chondrodistrophic breeds canines, being Dachshund the most predisposed to suffer this pathology. It is important to mention that it can appear in other breeds such as the Poodle, Basset Hound, Teckel, etc. This disease is mainly diagnosed when the animal is young, because it is an early degenerative condition of the intervertebral disc. This work describes the presentation of a five-year-old canine patient, Dachshund, who arrived to consultation with flaccid paralysis of the posterior limbs and lack of control of sphincters. A complete clinical- neurological examination and after that, a spinal x-ray were performed, confirming the diagnosis of such degeneration.
Keywords: condroid degeneration; pulpy nucleus; hydroelastic; condrodytrophic; x-ray.